The Ban on Veterinary Surgeons’ Advertising in Poland and European Union Law: An Analysis of the Compliance of National Regulations with EU Law (Ius Novum, 2026)
The purpose of this article is to analyse the compliance of Polish regulations prohibiting veterinary surgeons from advertising with EU law, particularly Directive 2006/123/EC on services in the internal market and Directive 2000/31/EC on certain aspects of electronic commerce. Particular attention is given to the impact of this compliance (or lack thereof) on disciplinary proceedings against members of the profession. The analysis indicates that Polish regulations, including Article 29 of the Act on Veterinary Facilities and Resolution No. 116/2008/IV of the National Veterinary Council, violate the EU principle of the free movement of services, specifically the right of veterinary surgeons to use commercial communications. This non-compliance necessitates the application of the principle of the primacy of EU law, meaning that disciplinary courts should consider EU regulations as ‘more lenient laws’ within the meaning of Article 4 § 1 of the Penal Code. The findings highlight the need to align Polish regulations with EU standards, ensuring that veterinary surgeons can use permissible forms of promotion in a manner consistent with professional ethics and the protection of the public interest.